The effects of varying cadence on sub-maximal heart rate, blood lactate and VO2 in elite male flatwater kayakers - Tyrrell, L.; Mahony, N.; Donne, B. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The aim of this study was to determine what effect a change in stroke rate on a kayak ergometer (Dansprint Ltd., Denmark) had on sub-maximal heart rate (HR), blood lactate (BLa) and oxygen uptake (VO2) data. Methods A total of 14 elite male kayakers were recruited and each subject was required to attend the laboratory twice for testing. On the first visit they were medically screened and anthropometric data were obtained. Following a standard 10-min warm-up (80W), a maximal incremental test was performed to ascertain data relating to performance and current fitness levels. During this test HR by radio telemetry (Cardiosport Ltd, Taiwan), VO2 by breath-by-breath analysis (Cosmed Ltd, Italy) and BLa data (YSI Ltd., USA) were recorded. Following a rest period, each subject performed a familiarisation session on the ergometer at the workloads (120 and 150 W) and cadences (70, 80 and 90 strokes.min-1) to be used in the second test session. On the second visit, each subject performed three-minute intervals on the ergometer at sub-maximal workloads of fixed cadences. Data was grouped and tabulated and repeated measures ANOVA was used to analyse differences in physiological variables with varying cadence, post-hoc analysis of significant differences were performed using Scheffe F-test, P<0.05 was considered significant. Results 7 of 14 subjects have completed the incremental and submaximal tests to date. The mean (±SD) age, 21 ± 4 years; height, 1.83 ± 0.03 m; body mass, 79.9 ± 4.6 kg. Mean (±SD) maximal performance data were VO2max, 63.9 ± 9.6 ml.kg.min-1; HR 190 ± 6 beats.min-1; VE 176.1 ± 26.2 L.min-1; BLa 9.8 ± 2.0mmol.L-1. There were no significant differences in blood lactate data across the three cadences at either workload. However, there was a significant difference in VO2 (P<0.05) between cadences 70 and 90 strokes.min-1 at 120 W. Heart rate data were also significantly different at the varying workloads and cadences. Conclusion These preliminary results suggest that there is a difference in physiological demand with a change in stroke rate at constant sub-maximal workloads. These were reflected in the changes demonstrated in both heart rate and oxygen uptake data. Blood lactate concentration did not demonstrate any significant changes when stroke rate on the kayak ergometer was altered at constant sub-maximal workloads.